Digital visual literacy the librarian's quick guide - Fox, Nicole M. (Santa Barbara, California Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2022)
"This book is designed to be a quick, informative guide to visual literacy instruction in any classroom (higher education), not just the art or design classroom. In order to connect visual literacy instruction to the digital space it now occupies, this book also features several workshops and instruction sessions that use digital humanities tools. Each chapter discusses a different facet of visual literacy through a digital lens"--Provided by publisher.
What is visual literacy? -- Identifying and finding images -- Evaluating and interpreting images -- Designing and communicating with images -- Citation and ethics for images -- Activities and assignments -- Conclusion -- Appendix. What if...? : common MLA citations and questions.
Includes bibliographical references and index.
Keywords: Visual literacy; Computer literacy.BC.; Digital humanities